Rede de atenção à saúde e cateterismo urinário: um diagnóstico situacional - Luvizutto, Julia (Universidade Federal de São Carlos, 2023)
To carry out a situational diagnosis of adult and juvenile users of urinary catheterization and their caregivers in the public Health Service (RAS) of a municipality in the interior of the State of São Paulo. Method: Quantitative, descriptive-exploratory, retrospective study, carried out with supervisors, managers and coordinators of health services regarding care for users using urinary catheterization. Data from the questionnaires were analyzed using descriptive statistics. Results: 38 health service managers from the RAS of the trained municipality were identified. Of the total health services in the RAS, 26.3% offer care for 23 users of urinary catheterization. Regarding the urinary catheter, 14 (61.0%) users have already used an indwelling urinary catheter and all have used an intermittent catheter. Of the users, they do not have caregivers, with the rest having family caregivers. Conclusions: Situational diagnosis constituted an essential strategy for creating contextualized interventions in health care. This study enabled the creation of multiple responses, both to face the production of health-disease in urology, and to identify relevant users, their clinical conditions and social context. Furthermore, it is possible to outline future research and technologies.
Health services and urinary catheterization: a situational diagnosis
Keywords: Atenção à saúde; Bexiga urinária; Cateterismo urinário; Cuidadores; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA